Dynamics of Nutrient Release and Transformations from Slow Release Fertilizers in Acid Rice Soils - Nisha P T (Department of Soil Science and Agricultural Chemistry, College of Horticulture, 1995)
A study was conducted to assess the pattern of release and transformation of major plant nutrients from slow release nitrogen fertilisers (SLNF) and to evaluate the efficiency of SLNF at the College of Horticulture, Vellanikkara, during 1992 – 94. Urea formaldehyde (UF), NP tablet (NP tab), NPK tablet (NPK tab), gypsum coated urea (GCU), blended urea ammonium sulphate (UAS) and magnesium ammonium phosphate (MAP) were compared with no (NF) and recommended dose of fertilisers (C). Evaluations were conducted with four acid soils viz., laterite, kari, Kuttanad alluvium and costal sandy kept under incubation for six months and a pot culture study using laterite soil and rice variety Jyothi during puncha season. The release of ammoniacal nitrogen (NH4 – N) was found maximum in kari soil, followed by kuttanad alluvium and laterite and the lowest in sandy soil. Release of nitrate nitrogen (NO3 – N) was maximum in the earlier periods in the case of sandy and laterite soils with lower release at later stages. In the case of kari and Kuttanad alluvium the trend was opposite with higher release at later intervals and lower release at early periods. In general nitrification was found to be low in all the soils. Irrespective of the soil types, the maximum content of NH4 – N was recorded by the NPK tab which was closely followed by MAP, whereas the maximum NO3 – N was registered by MAP. For these two different forms of nitrogen, the minimum values were always found in the NF treatment. The available P content of the soil recorded significant variation throughout the period incubation. Among the treatments MAP and UAS recorded the maximum values and NPK tab the minimum P content. Irrespective of the soil types, there was uniformity in the release of available K throughout the incubation period. In pot culture trial NH4 – N decreased as crop stages advanced. With NO3 – N, an initial decrease followed by an increase at harvest stage was noticed. The treatment GCU recorded maximum NH4 – N and NO3 – N content, while NF the minimum. There was decrease in available P and K contents of the soil as the crop growth proceeded. Significant influence on morphological observations were also recorded with MAP maintaining superiority over other treatments. Maximum dry matter, straw and grain yield were recorded respectively by the treatments UAS, C and MAP. Uptake of N, P and K were also influenced significantly with MAP registering the highest and NF the lowest values. Both NP and NPK tab recorded lower values. Maximum leaching loss of N and P were seen with the control and the minimum with MAP whereas it was respectively with UF and NPK tab for K. The total N recovery percentage, was recorded in the decreasing order : MAP > C > UF > GCU > UAS > NP tab > NPK tab. There was a decreasing order of MAP > UAS > UF > GCU > C > NPK tab NP tab for N response of different treatments under study.